Modes of Delivery in Services - Elisabeth Christen; Joseph Francois (Johannes Kepler University of Linz, Department of Economics, 2010)
We develop a new analytical framework for both cross-border services trade and services trade through foreign affiliates, based on heterogeneous firms operating under oligopoly. This leads to direct predictions about choice of services delivery (mode of delivery) at the firm level, and about the pattern of bilateral trade at the industry level. We examine the industry-level predictions, working with a panel of U.S. data. Unlike the recent literature that works with FDI as a proxy for affiliate services sales, we work directly with data on bilateral U.S. trade through affiliates. These data feature more sector detail than in the recent literature. We also directly compare observed patterns of services trade and affiliate sales with the corresponding indicators of patterns of cross-border and affiliate sales for manufacturing sectors. In contrast to mixed results in manufacturing, in services overseas multinational activities consistently increase relative to direct exports the further away are host countries. Language and the presence of manufacturing FDI are also important. The impact of factors like corporate tax rates and relative stocks of human capital on modes of service delivery varies across sectors. The evidence on interdependence across modes and the importance of local affiliates implies that the impact of policy in any one mode is likely to depend on the mix of domestic regulation and policy across all modes of supply.
Keywords: F10; F14; F23; L80; 330; International trade in Services; Modes of Supply; FDI; Foreign Affiliates Trade; GATS; Direktinvestition; Ausländische Tochtergesellschaft; Dienstleistungsmanagement; Internationaler Dienstleistungsverkehr; GATS; USA